ALIGNMENT OF BUSINESS STRATEGY AND SUPPLY CHAIN MANAGEMENT: a study of medium-to-large-sized internationalized German companies from an international business student perspective - Fölsch, Carmen (My University, 2017)
In an increasingly globalized world, effective supply chain management and its alignment with a company’s business strategy is seen as a firm’s competitive advantage. Existing studies, which were conducted in internationally known companies, suggest three main strategies: Lean, agile and leagile supply chain strategies. Lean supply chain strategies in markets with a stable demand follow a cost-minimizing approach. Agile supply chain strategies in markets with an unpredictable demand focus on differentiation, innovation and flexibility in order to fulfill customer-specific demand. Finally, leagile supply chain strategies try to combine lean aspects for a base demand and agile aspects for more customer specification. This study researches internationalized medium-to-large-sized German companies with the purpose of understanding how companies can improve their supply chain management from an international business perspective. Results are based on the analysis of qualitative data collected through 14 semi-structured interviews with employees from the SC or business department. Findings suggest that lean, agile and leagile supply chains exist as described in the literature. Furthermore, the supply chain strategies called ‘project’ SC and ‘capable’ SC were found. Project SCs are used for a fixed period of time in order to conduct customer-specific ventures. They are a specialized version of agile SCs with the difference that they are constructed from scratch. Capable SCs are characterized by delivery reliability and speed and customer closeness in markets with predictable demand. They can be considered an advancement of leagile SCs. Furthermore risk- hedging SC management was researched. Moreover, the changes in strategies over the years were examined and the meaning of increased automation and usage of computerized systems in the context of industry 4.0 were questioned. The results show that changes and technology play different roles according to industry. In conclusion the findings cannot be generalized due to the small sample size. However, the results give an insight into current supply chain management strategies that can lead to the practical implication of integrating the customer more in the SC. In the future SCs could have increased transparency, flexibility, and simultaneity. Further quantitative research is recommended.
Keywords: Supply chain management; Business strategy; German companies; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|